Experimental Development Process of a New Cement and Gypsum-Cemented Similar Material considering the Effect of Moisture - Chai, Jing; Wang, Shuai; Chen, Shaojie; Liu, Qi; Zhang, Dingding (Geofluids, 2020)
A new type of similar material considering water characteristics is developed through orthogonal experiments. The similar material is composed of river sand, barite powder, cement, gypsum, and water. We determine the best test development process. First, the proportion test scheme is designed based on the orthogonal test. Then, the effects of the moisture content, mass ratio of aggregate to binder and other components on the density, uniaxial compressive strength, elastic model, and Poisson’s ratio of similar materials are analyzed by range analysis. Finally, the multiple linear regression equation between the parameters and the composition of similar materials is obtained, and the optimal composition ratio is determined according to the relationship between the test’s influencing factors and the mechanical properties of similar materials. The results show that the selected raw materials and their proportioning method are feasible. The content of barite powder plays a major role in controlling the density and Poisson’s ratio of similar materials. The mass ratio of aggregate to binder is the main factor that affects the uniaxial compressive strength and elastic modulus of similar materials, while the moisture content has the second largest effect on the density, uniaxial compressive strength, elastic modulus, and Poisson’s ratio of similar materials. When the residual moisture content increased from 0 to 4%, the uniaxial compressive strength and elastic modulus of similar materials decrease by 49.5% and 53.3%, respectively, and Poisson’s ratio increases by 54.8%. Determining the residual moisture content that matches the design of similar material model tests is critical to improving the test accuracy and provides a reference to prepare similar materials with different requirements.